THE INFLUENCE OF SERVICE QUALITY TO CUSTOMER SATISFACTION IN BIG POST OFFICE PONTIANAK - Siti Nurmala; Aminuyati Aminuyati; Warneri Warneri (Universitas Tanjungpura, 2022)
Abstract The purpose of this research is to know the service quality that big post office Pontianak give, customersatisfaction that big post office Pontianak give andthe influence of service quality to the customer satisfaction in big post office Pontianak. The factors that influence service quality in big post office Pontianak such as Tangible, Reliability, Responsiveness, Empathy, Assurance, the service quality to the customer satisfaction. This research used data obtained from the distribution of questionnaires. The sampling technique in this study is insidental sampling. The number of samples obtained by 50 people in big post office Pontianak. The distribution of questionnaires obtained by 50 people for efficiency of the research when Covid 19, to get the good result and was helping the post officepart. The data analysis technique used in this research is multiple linear regression.In multiple linear regression of hypothesis testing using F-statistics, tstatistics, andR 2 . The result of this study show that service quality in big post office Pontianak isvery important for people pulse. For the result effect of service quality to customersatisfaction based on multiple linear regression analysis show that tangible factorhas a negative influence and significant to customer satisfaction in big post office Pontianak and based on t statistic, t statistic is -2,323 and significance is 0,025. Reliability factor has a positive influence and not significant to customer satisfaction in big post office Pontianak and based on t statistic, t statistic is 1,808and significance is 0,077. Responsiveness factor has a positive influence and not significant to customer satisfaction in big post office Pontianak and based on t statistic, t-statistic is 1,415 and significance is 0,164. Empathy factor has a negative influence and significant to customer satisfaction in big post office Pontianak and based on t statistic, t statistic is - 3,739 and significance is 0,001. Whereas, assurance factor has a positive influence and significant to customer satisfaction inbig post office Pontianak and based on t statistic, t statistic is 1,475 and significanceis 0,047. Based on F-statistic show that F statistic more than F table ((4,304>2,50)with the significance small than 0,05 so that independen variable (service quality)has a significant influence to dependen variable (customer satisfaction). And basedon coefficient determination is 32% dependen variable able to predicted by the independen variable and 68% is influence by other factor beside research model. Keywords: Customer Satisfaction, Service Quality